Development of a food safety policy framework for Kenya: Lessons and best practices from the Vietnam experience - Kang'ethe, Erastus K.; Muriuki, Samuel; Karugia, Joseph T.; Guthiga, Paul M.; Kirui, Leonard (International Livestock Research Institute, 2019)
Food safety is gaining traction in Kenya due to growing public health concerns for domestic and international trade. Past efforts to establish a food safety management system and a coordination mechanism have not borne fruit. Thus, ongoing efforts and advocacy initiatives are seeking greater science-based evidence to convince policy makers and stakeholders to take the issue of food safety more seriously. This report reviews the process adopted by the Government of Vietnam in developing its food safety policy framework with the view of drawing lessons and best practices that Kenya could consider in its own efforts to develop a modern food safety policy framework. The process followed in Vietnam was driven by the felt needs of the general public. These needs attracted the political will and leadership of the highest office in the land to initiate an inclusive agenda to improve food safety management in the country (domestic and export market). The Kenya process requires: i) building on the big four agenda—that includes access to adequate safe food (food security) and health for all—to which the country’s top leadership is committed; ii) convening of an inclusive multi-stakeholder approach with the participation of local and international players in food safety to drive a modern food safety framework using science-based evidence to target priority food safety issues of the key value chains for domestic and international markets; and iii) establishing an effective, well-coordinated, accountable, adequately resourced and responsive risk-based food safety control system (with a clear policy, legal framework, institutions, fit for purpose laboratories and a monitoring system) and a foodborne diseases/illnesses surveillance system. The Food Control System should be supported by sustainable capacity development and retention to guarantee effective delivery.